Os acordos sobre o comércio de bens e o imposto de importação no âmbito da Organização Mundial do Comércio - Menezes, Renata Sousa Amorim (2025)
International trade has consolidated over recent decades as a strategic driver of global economic development, with multilateralism serving as a central element in coordinating trade relations among states. This research examines the evolution and role of the main international agreements regulating the trade of goods within the multilateral trading system, highlighting their importance in consolidating a global trade framework guided by the principles of non-discrimination, transparency, and regulatory predictability. From this perspective, the present dissertation analyzes the influence of multilateral agreements on the trade of goods, particularly regarding import duties, considering both international normative frameworks and the implementation of these rules within national legal systems. It was evidenced that multilateralism is not limited to a normative ideal but constitutes a pragmatic instrument for coordinating and harmonizing economic policies, consolidating rules that govern the flow of goods, services, and capital. The effectiveness of the system therefore requires institutional innovation and political commitment, emphasizing that the existence of rules must be accompanied by their equitable and coordinated application. The study underscores that the effectiveness of the multilateral system is conditioned upon states’ capacity to internalize its norms, through the implementation of compatible policies and respect for decisions rendered by the various WTO bodies. Such internalization fosters predictability, mutual trust, and macroeconomic stability, transforming import duties and trade agreements into regulatory instruments capable of balancing national and global interests, mitigating discriminatory practices, and promoting economic cooperation. In summary, the research reaffirms that multilateralism is an indispensable pillar of international trade, whose historical evolution, institutionalization, and operationalization through the WTO ensure predictability, equity, and economic efficiency. Trade agreements and import duties, when regulated multilaterally, play a central role in global governance, consolidating an environment of cooperation and stability essential to contemporary international trade.